Development of Animated Videos Based on Character Educationon Learning Indonesian Language is in Low Class - Amelia Putri; Lathifa Munawarah (Berpusi Publishing, 2024)
This research explores the development of animated character education videos in Indonesian language learning in lower grades. Using development research methods, we design, produce and evaluate animated videos that are integrated with the Indonesian language curriculum. The results showed positive responses from teachers and students, showing the potential of animated videos to improve understanding of the material. These findings highlight the relevance of this innovation in improving the quality of Indonesian language learning in elementary schools. This study provides a basis for further development in integrating character education through animation media in the context of basic education.